Maternal Mortality, Dublin, 1864–1902. (21st March 2017) - Breathnach, Ciara; Gurrin, Brian
Summary: Using civil registration as a prism this article examines the complicated interface between the authorities, medical professionals, women in childbirth and the aftermath of delivery. It argues that Irish maternal mortality was underestimated and provides a number of arguments in relation to the complex socio-medical environment to explain why. Our research shows how a combination of cavalier attitudes towards cause of death classification and liberal interpretations of William Farr's Statistical Nosology, served to obscure the true extent of maternal mortality in Dublin City from 1864 to 1902. By offering a microhistory of maternal mortality reporting and registration this article problematises the merits of using civil registration data as a resource for the social history of medicine.